You know you love me : a Gossip Girl novel - Von Ziegesar, Cecily (Boston : Little, Brown, 2003)
Blair and Serena, who go to an exclusive private school in Manhattan, are no longer best friends but are still both consumed with thoughts of boyfriends and college.
Keywords: High schools -- Fiction; Schools -- Fiction; New York (N.Y.) -- Fiction